Analyzing Elementary English Teachers’ Pronunciation Errors: Are We Intelligible? - Dedi Febrianto (STAI Hubbulwathan Duri, 2021)
Error analysis on students’ language performance has been massively discussed, yet few studies focused on teachers’ errors. Meanwhile, one of the main causes of students’ errors is the errors transferred from teachers. As the learners used to imitate their teachers sounds’ production, EFL teachers need to minimize errors when teaching at elementary school concerning the learners’ best period to acquire and learn a foreign language. The present study investigates EFL teachers’ pronunciation errors, specifically to find out the forms and causes of pronunciation errors in segmented vowels produced by the teachers. The research participants are 20 English teachers selected from various public and private elementary schools in Yogyakarta who were invited to pronounce 62 English words. The teachers were also required to fill out a questionnaire to find out external factors which are assumed can trigger the errors. The findings delineated that the teachers produced various forms of pronunciation errors in English vowels. The causes of errors lie in interlingual transfer, intralingual transfers, pronunciation differences between graphemes and sounds, hypercorrection, and words similarity. The external factors are also scrutinized, which include educational background and teachers’ lack of English practice. The study suggests that elementary EFL teachers in Indonesia should improve their pronunciation by frequently practicing and having intensive pronunciation training to teach better English to their learners.